Próba zastosowania zmiennej syntetycznej z medianą do analizy lokalnego rynku pracy - Witkowska, Aleksandra; Witkowski, Marek (The Analysis of Local Labour Market with the Use of Synthetic Variable with Median, 2008)
In the analysis below to estimate the local labour market, we used the synthetic variable based on median. Having taken into consideration the fact that there are a lot of diagnostical attributes, which describe this market, we think that this variable will be very useful. We also think that the measurement of labour market while using this synthetic variable gives more reliable results than the measurement based only on an unemployment rate.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 7, s. 416-425